AB248. SOH26AB_0385. An evaluation of the acceptability of patient-initiated review (PIR) in sarcoma follow-up: a mixed-methods study - Bissoonauth, Thayumaan; McIntyre, Tom; Hayden, Una; Ridgway, Paul (Mesentery and Peritoneum; Vol 10 (April 30, 2026): Mesentery and Peritoneum (Abstracts for the Sylvester O'Halloran Perioperative Symposium 2026), 2026)
Follow-up for sarcoma survivors is traditionally delivered via routine, hospital-scheduled clinics. Patient-initiated review (PIR) may reduce low-value visits along with their associated carbon footprint, but evidence of acceptability amongst sarcoma survivors is limited. We evaluated PIR in sarcoma follow-up.